Tracking bacterial infection into macrophages by a novel red-emission pH sensor - Jin, Yuguang (2010)
The relationship between bacteria and host phagocytic cells is a key to the induction of immunity. To visualize and monitor bacterial infection, we developed a novel bacterial membrane permeable pH sensor for noninvasive monitoring of bacterial entry into murine macrophages. The pH sensor was constructed using 2-dicyanomethylene-3-cyano-4,5,5-trimethyl-2,5-dihydrofuran (TCF) as an electron-withdrawing group and aniline as an electron donating group. A piperazine moiety was used as the pH sensitive group. Because of the strong electron donating and withdrawing units conjugated in the sensing moiety, M, the fluorophore emitted at red spectral window, away from the auto-fluorescence areas of bacteria. Following the engulfment of sensor-labeled bacteria by macrophages and then merging with host lysosomes, the low pH environments will enhance the fluorescence intensity of the pH sensors inside the bacteria. Time-lapse analysis of the fluorescent intensity suggested significant heterogeneity of bacterial uptake among macrophages. In addition, qRT-PCR analysis of the bacterial 16S rRNA gene expression within single macrophage cells suggested that the bacteria have been engulfed into macrophages and their 16S rRNA is still intact after 120 min. Toxicity assay showed that the pH sensor has no cytotoxicity on either E. coli or murine macrophages. The sensor shows good repeatability, a long lifetime and a fast response to pH changes, and can be used for a variety of bacteria.